PENGARUH SUHU DAN KELEMBABAN TERHADAP POPULASI ARTHROPODA PADA LAHAN APLIKASI DAN TANPA APLIKASI LIMBAH CAIR PABRIK KELAPA SAWIT - Sakiah Sakiah; Mariani Sembiring (Jurnal Agro Estate, 2018)
Arthropods play a role in the decomposition process of organic matter. The existence of arthropods in soil is aﬀected by environment. This research is aiming to find out the temperature of humidity and population of arthropods in a diﬀerence distance from the plate and ditch of application towards application field and without application of palm oil mill eﬄuent (POME). The research is done in Bukit Maradja Estate, PT. SIPEF in April to August 2017. The research design is used random design of factorial group, the fist factor is the sampling area, the second factor is the distance from the plate to the application ditch. The parameter testing arranged on the list of variance and Least Significance Diﬀerence (LSD) test, with 5% value. The research result showed temperature and population of arthropods is no diﬀerent between application area and without application area (POME), while soil humidity showed significance diﬀerence between application area and without application area (POME). Temperature, humidity and population of arthropods has no significance diﬀerence in sampling area 0cm, 100cm, 200cm, 300cm and 400cm from plate edge and POME application ditch. The number of arthropods is aﬀected by temperature and soil humidity. In application area of POME was found 5 classes of arthropods and 34 species. Population of arthropods in POME application area is 261 individuals and without POME application is 146 individual.